The applicability of International Financial Reporting Standard IFRS 18 (Presentation and Disclosure in Financial Reports) and its impact on improving financial performance: An analytical study of a sample of commercial banks listed on the Iraq Stock Exchange - Qurbani, Zana Ahmed Abdullah; Najm, Asst.Prof.Dr. Basira Majeed (Sulaimani Journal for Humanities, 2026)
This research aims to demonstrate the impact of applying International Financial Reporting Standard (IFRS 18) on the presentation and disclosure in the financial reports of banks listed on the Iraq Stock Exchange, and to show the extent to which this reflects on improving the presentation and analysis of financial performance. The importance of this research stems from the fact that IFRS 18 was introduced to improve the presentation of financial statements, particularly the profit and loss statement, by reclassifying revenues and expenses, highlighting sub-totals more clearly, and enhancing the disclosure of information that helps investors and stakeholders better understand financial performance. The research was applied to the financial data for the period 2023-2024 for Bank of Baghdad and the National Bank of Iraq, both listed on the Iraq Stock Exchange. The research relied on comparing several operational efficiency and profitability indicators according to IAS 1 and IFRS 18, the most important of which are net interest margin, operating profit margin, EBITDA margin, asset utility ratio, return on assets, and return on equity. The research reached several conclusions, most notably that the application of IFRS 18 did not lead to changes in indicators related to net profit, average assets, and equity, while its impact was more pronounced in operational indicators due to reclassification and re-presentation. The results also showed that the standard's impact was not uniform across all cases. Some indicators improved in certain years, while others declined slightly, indicating that the accounting presentation method influences the interpretation and analysis of financial performance. The research concluded with several recommendations, the most important of which are the need to prepare Iraqi banks for the early implementation of IFRS 18, review the classification of revenues and expenses, develop financial reporting models, and train accounting and auditing staff on the standard's requirements and its application within the banking environment.
Keywords: International Accounting Standards IAS 1; International Financial Reporting Standards IFRS 18; Financial Performance; Financial Reporting; Presentation and Disclosure